Analysis of Lignin Isolated from Alkaline Leaching of Alfa Grass - Aroua, S.; Lounis, A.; Condom, S.; Semaoune, F. (Asian Journal of Chemistry, 2010)
The analysis of Alfa grass lignin is examined, isolated from industrial black liquor of the Algerian Pulp and Paper Company using the soda process. The used experimental techniques are: UV/visible, microscopy (MEB), FTIR, spectroscopy, EDAX and for the first time, HPLC (high performance liquid chromatography), MS (mass spectrometry) and GC/MS (coupled gas chromatography/mass spectrometry) analysis that permit us the valorization of this product.